Thus spake Zarathustra : a book for all and none - Nietzsche, Friedrich Wilhelm, 1844-1900 (Classics series., 2003)
Zarathustra was Nietzsche's masterpiece, the first comprehensive statement of his mature philosophy, and the introduction of his influential and well-known (and misunderstood) ideas including the "overman" or "superman" and the "will to power." It is also the source of Nietzsche's famous (and much misconstrued) statement that "God is dead." Though this is essentially a work of philosophy, it is also a masterpiece of literature, a cross between prose and poetry. A considerable part and parcel of Nietzsche's genius is his ability to make his language dance, and this is what becomes extraordinarily difficult to translate. It has been almost 40 years since Hollingdale's version for Penguin and almost 50 since Kaufmann's. However, anyone who appreciates the German original knows that these translations are merely adequate. While earlier translators have smoothed out the rough edges, cut corners and sometimes omitted troublesome passages outright, this one honors and respects the original as no other. Kaufmann and others are guilty of the deplorable tendency to "improve" on the original. Much is lost by this means, to say nothing of the interior rhythms, the grace notes, the not always graceful but omnipresent and striking puns and wordplays. And in not a few instances the current translation improves on Kaufmann's use of English or otherwise clarifies what Nietzsche is really saying